Autonomy of Biology and Non-reductionism in the Biophilosophy of Francisco J. Ayala - Espinosa, Diego Cano (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Reductionism is a very recurrent issue in the epistemology of Biology; this simplification is sometimes improperly carried out by positivist scientists. Professor F. J. Ayala refers to them when he speaks of the impossibility of total scientific reduction on three levels: ontological, methodological, and epistemological. The autonomy of the biological sciences is slowly confirmed by researchers who realizethe insufficiency of explanations from experiments obtained from an analysis of lower levels. This insufficiency arises when no recourse is made to superior levels that also form part of biological realities. In this context, the contributions of modern vitalism or organicism, emergentism and the new organicist theories are relevant. In order to describe a living organism, biochemical and biomolecular analyses are not sufficient, since a synthetic view of the lower and superior levels is also necessary. We can have a better knowledge of living organisms if we take into account not only their physico-chemical basis, but also the processes taking place at the organic level.
Keywords: autonomy; reductionism; mechanicism; vitalism; emergentism; holism; organicism; organic level; compositionism; epigenesi